The Potential Development of Pandua Beach Tourism Objects in Nainggolan District Samosir Kabupaten Regency - Sumihar Sebastiana Sitompul (Politeknik Pariwisata Medan, 2021)
The purpose of this study is to analyze the factors that influence the constraints in developing Pandua Beach tourism objects, where some of the obstacles faced consist of several factors where the ability of the surrounding community does not fully understand about good service for visitors who come. The research method used in this study is to use SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) which is an analytical method that will describe the strengths, weaknesses, opportunities and threats as well as the constraints that must be faced in a development process. The results of this study Pandua Beach has a beautiful panorama, pristine and cool, has a strong appeal of diversity, the community has openness to local and foreign tourists, relatively cheap food prices, good security conditions, already has a place for culinary tourism facilities. . Opportunity factor (Opportunity); Tourists easily reach the location, the more cooperative the tourism office and other agencies for the development of Pandua beach attractions, the flow of technology and information development is getting stronger, the location of the Nainggolan sub-district is strategic, the local government strongly supports the entry of investment for tourism development Supporting factors; Beautiful natural panorama, cool and pristine, openness of society to tourists, good security conditions, already has tourism for culinary, sloping beaches and clear water. Inhibiting Factors; constraints on land development to be used as tourist attractions, do not have uniqueness/attractions, people are still difficult to give up their land to develop tourism objects. Provision of public transportation facilities to reach the object to support the development of tourism objects. Utilization of information technology needs to be done to introduce and promote the potential of each tourist attraction to the wider community. In addition to introducing it to the wider community, the use of information technology can also attract investors to actively contribute to the development of Pandua Beach tourism objects.